Độ phức tạp otomat hữu hạn đoán nhận siêu ngôn ngữ chính quy - Ruận, Đặng Huy; Ổn, Phùng Văn (Journal of Computer Science and Cybernetics, 2016)
We shall call the  small possible number of states of a hyper-finite deterministic automaton, which recorgnizes the set of word L in the alphabet ∑, a complexity of a finite automaton of L, and denote by P(L). We have the following result: For any hyper-generating schemar G, the complexity of a finite automaton of L(G) is: P(L(G)) ≤ 2 D + 1.